RELATIONSHIP BETWEEN ANEMIA AND ABORTION IN PREGNANT WOMEN AT RSIA ANANDA MAKASSAR 2021-2022 - Azzahrah, Nurfauziah; Rahim, Rosdianah; Fauziah, Henny (E-Jurnal Medika Udayana; Vol 13 No 1 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i01.P16, 2024)
Abortion is a condition of pregnancy that ends when the gestational age is less than 20 weeks or the fetus has not been able to live outside the womb. The purpose of this study was to determine the relationship between anemia and the incidence of abortion in pregnant women at the Ananda Mother and Child Hospital Makassar in 2021-2022. This type of research is analytic observational research with a case control study approach. The sampling method used purposive sampling was divided into 102 case samples and 102 control samples. The data consists of being obtained from the medical records of RSIA Ananda Makassar for 2021-2022. Anemia as the independent variable and  abortion as the dependent variable. Data were analyzed by univariate test and bivariate test by chi-square test. The research results obtained a p-value of 0.004 (p <0.05) and an OR value of 3.312. The conclusion in this study is that anemia is significantly related to the incidence of abortion at RSIA Ananda Makassar in 2021-2022. Keywords: Anemia, Abortion